Deaths of bicycle riders in Brazil: characteristics and trends during the period of 2000 - 2010 - Leila Posenato Garcia; Lúcia Rolim Santana de Freitas; Elisabeth Carmen Duarte (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
INTRODUCTION: In Brazil, bicycle use has been increasing. Accidents involving cyclists are important causes of morbidity and mortality. OBJECTIVE: To describe the mortality of cyclists injured in transport accidents in Brazil, the characteristics of the victims and of the occurrence, and to investigate its trends during the period between 2000 and 2010. METHODS: A descriptive study with data from the Mortality Information System (SIM) was conducted in the period of 2000 - 2010. Crude and age-standardized corrected mortality rates were calculated for Brazil, its macro-regions and states. Linear regression was used to study the trends. RESULTS: In the period of 2000 - 2010, 32,422 bicycle-related deaths were identified in Brazil. In 2010, there were, on average, 8.8 bicycle-related deaths per day. Age-standardized mortality rates for the country were 15.3 and 15.9 deaths per million inhabitants in 2000 and 2010, respectively (p = 0.725). During the whole period, the Center-Western region showed the highest rates, though stable, corresponding to 23.4 deaths per million inhabitants in 2010. Men accounted for 85.4% of deaths, with death risk 5 times higher than women. CONCLUSION: In spite of the stable rates for the country, there was an increase trend in the Northern and Northeastern regions, while a decreasing trend was observed in the Southern and Southeastern regions. The risk of death was higher among men, elderly, and people living in large cities and at the Center-Western region.